Occurrence, transmission and genotype response of a filamentous virus associated with leaf mustard (Brassica juncea var. rugosa) in Manipur - L. RANJANA DEVI; M.L. DAS, PH.SOBITA DEVI, A.I. BHAT* (Indian Phytopathology, 2004)
A mosaic disease of leaf mustard (Brassica juncea var.rugosa) was found widespread in different locations of Manipur (upto 90.50%)and prevalent in the market samples from different sources (upto 89.58 %). Disease incidence was low during October-November and high during February-March months. The causal virus was transmissible by sap (7.88%) and by three species of aphid (Myzus persicae Sulz, Lipaphis erysimi Kalt and Brevicoryn brassicae L.) but not through seeds. Electron microscopic examination revealed the virus to be flexuous rod shaped particles with an average particle length of 735nm. Out of six local genotypes tested, Hangam- Lamtachabi and Hangam – Apakpi were found to be resistant to the disease. This is the first report of the occurrence of the mosaic disease in leaf mustard in Manipur.